Amino acid polymorphisms in Arabidopsis phytochrome B cause differential responses to light - Filiault, Daniele L. (National Academy of Sciences, 2008)
Plants have a sophisticated system for sensing and responding to their light environment. The light responses of populations and species native to different habitats show adaptive variation; understanding the mechanisms underlying photomorphogenic variation is therefore of significant interest. In Arabidopsis thaliana, phytochrome B (PHYB) is the dominant photoreceptor for red light and plays a major role in white light. Because PHYB has been proposed as a candidate gene for several quantitative trait loci (QTLs) affecting light response, we have investigated sequence and functional variation in Arabidopsis PHYB. We examined PHYB sequences in 33 A. thaliana individuals and in the close relative Arabidopsis lyrata. From 14 nonsynonymous polymorphisms, we chose 5 for further study based on previous QTL studies. In a larger collection of A. thaliana accessions, one of these five polymorphisms, I143L, was associated with variation in red light response. We used transgenic analysis to test this association and confirmed experimentally that natural PHYB polymorphisms cause differential plant responses to light. Furthermore, our results show that allelic variation of PHYB activity is due to amino acid rather than regulatory changes. Together with earlier studies linking variation in light sensitivity to photoreceptor genes, our work suggests that photoreceptors may be a common target of natural selection.